Er2O3 coating by reactive magnetron sputtering: Effect of oxygen supply and erbium pre-layer deposition. (December 2016) - Rayjada, P.A.; Vaghela, N.P.; Rahman, R.; Bhatnagar, M.; Ranjan, M.; Chauhan, N.L.; Sircar, Amit; Manocha, L.M.; Raole, P.M.
Highlights: O2 /Ar feed ratio is varied in reactive sputter coating of erbia. Higher O2 /Ar feed ratio gives higher roughness and superior crystallization Er pre-layer deposition induces film growth in cubic phase at 500 °C temperature. In absence of Er pre-layer, only monoclinic phase grows, even at 600 °C temperature Ellipsometry gives encouraging result for non-destructive characterization of film Abstract: Erbium oxide (erbia/Er2 O3 ) is one of the leading candidate coating types to address the issues of tritium permeation reduction and Magnetohydrodynamic (MHD) drag reduction in fusion reactor with liquid Lead–Lithium (Pb–Li) or molten salt Flibe (2LiF + BeF2 ) as the coolant and breeder materials. The electrical resistivity, hydrogen/deuterium permeation reduction property, liquid metal corrosion, radiation effects and deposition techniques are major areas of research on erbia coating. Though it is having a single stable phase of cubic structure up to 2300 °C, it is known to develop metastable monoclinic phase especially in sputter coating methods. We grow erbia by reactive magnetron sputter coating method and study the phase formation, electrical, microstructural and optical dielectric properties. The effects of erbium metal pre-layer deposition, post annealing in oxygen rich vacuum and oxygen to argon gas feed ratio are studied keeping other parameters constant. The film grows in mixed phase of cubic and monoclinic structures when erbium metal pre-layer is deposited on the P91 steel substrate and in pure monoclinic phase in absence of the pre-layer. Post annealing seems to partially convert monoclinic into cubic phase in the mixed phase coating. Better crystallization and slightly more surface roughness is observed in the sample processed with higher oxygen to argon ratio. DC resistivity is found in 10 15 Ω * cm range and it is marginally more in the sample processed with more oxygen. The spectroscopic ellipsometry on these films to obtain optical dielectric properties gives encouraging results in terms of close match of the thickness and roughness values with those obtained from SEM and AFM respectively. Systematic study of optical dielectric property suggests a trend consistent with DC resistivity.